2023
DOI: 10.21203/rs.3.rs-2456709/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antimicrobial resistance of Vibrio cholerae O1 strains isolated during cholera epidemics in eastern Democratic Republic of Congo between January 2011 and June 2022

Abstract: Background Although the mainstay of cholera treatment remains rehydration, treatment with antibiotics is recommended in serious forms and on specific sites. However, since the late 1970s, resistance to antibiotics in strains of Vibrio cholerae (Vc) has been observed and now threatens the effective treatment and control of cholera. Objective and Methods This cross-sectional, retro-prospective, descriptive and analytical study aims to describe the long-term evolution of the antibiotic resistance profile of Vibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Moreover, in several other studies, ciprofloxacin, doxycycline, and azithromycin remained the most sensitive molecules. This corresponds to data from the WHO and the GTFCC which re- cently recommended the use of the five molecules in the management of cholera, namely fluoroquinolones (ciprofloxacin), cyclins (doxycycline, tetracycline) and macrolides (azithromycin, erythromycin) [27]. Taking this WHO recommendation into account in our study, according to the antibiogram data, we found 27 different resistance profiles representing 3515 strains of Vibrio cholerae O1.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, in several other studies, ciprofloxacin, doxycycline, and azithromycin remained the most sensitive molecules. This corresponds to data from the WHO and the GTFCC which re- cently recommended the use of the five molecules in the management of cholera, namely fluoroquinolones (ciprofloxacin), cyclins (doxycycline, tetracycline) and macrolides (azithromycin, erythromycin) [27]. Taking this WHO recommendation into account in our study, according to the antibiogram data, we found 27 different resistance profiles representing 3515 strains of Vibrio cholerae O1.…”
Section: Discussionsupporting
confidence: 81%